Enzyme additions to sorghum-based diets for finishing pigs - Park, J.S.; Hines, Robert H.; Maloney, C.A.; Cao, H.; Lee, D.J.; Hancock, Joe D.; DeRouchey, Joel M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three experiments were conducted to determine the effects of a sorghum-specific enzyme supplementation on growth performance of finishing pigs. Although positive trends occurred, the sorghum-specific enzymes used in our experiments did not yield large and(or) consistent improvements in growth performance or nutrient digestibility in finishing pigs.
Keywords: Swine; Sorghum; Enzyme; Finishing pigs